A systematic approach to assessing novelty, requirement satisfaction, and creativity. Issue 4 (5th October 2018) - Ranjan, B.S.C.; Siddharth, L.; Chakrabarti, Amaresh
Abstract: It is well-known that creativity is crucial for sustaining a product against competition. Many factors have been proposed in the literature as indicators of creativity, among which outcome-characteristics-based factors are considered the most reliable; among these, the creativity of an outcome is often indicated by two major factors: novelty and usefulness . Only a few studies address as to how creativity assessment methods and their results can be used during the design process. To systematically address the issue of how to influence creativity of design solutions, the following questions have been framed. (1) Which factors should be used as indicators of creativity consistently across different phases of the engineering design process? (2) How can creativity be assessed in terms of these factors during the engineering design process? In this work, we consider novelty and usefulness as the necessary factors for creativity . It is found, however, that it is not possible to directly assess the usefulness of outcomes during the design process. Therefore, requirement satisfaction is used as a proxy for usefulness . We propose a creativity assessment method that uses novelty and requirement satisfaction as indicators for creativity; the method can be used for assessing not only complete products but also ideas or concepts, as they evolve through the phases of the design process. The application of the method in design is explained using a detailed example from a case study.